Comparative Analysis of Glycosidic Aroma Compound Profiling in Three Vitis vinifera Varieties by Using Ultra-High-Performance Liquid Chromatography Quadrupole-Time-of-Flight Mass Spectrometry - Wei, Yi; Chen, Zhuo; Zhang, Xin-Ke; Duan, Chang-Qing; Pan, Qiu-Hong (Frontiers in Plant Science, 2021)
Glycosidic aroma compounds are important precursors of volatile aroma in grapes, and they can be released to odorous aglycones via enzyme- or acid-catalyzed hydrolysis during wine fermentation and storage. Developing an analytical method for intact glycosides can offer the possibility to study the accumulation of these aroma precursors in grape berries. For this purpose, a MS/MS database based on ultra-high-performance liquid chromatography quadrupole-time-of-flight mass spectrometry (UHPLC-Q-TOF-MS) was built, covering multiple aglycone classes. Subsequently, the profiles of glycosidic aroma compounds in Vitis vinifera L. cv ‘Muscat Blanc’, ‘Riesling’ and ‘Chardonnay’ berries during maturation were dissected. Pentosyl-hexosides were the most abundant glycosides in three varieties. Both composition and concentration of glycosidic aroma compounds varied obviously among grape varieties. Except for monoterpenol pentosyl-hexosides, most glycosides kept almost stable in their concentrations during berry maturation. This research provides an approach to understand the variation of glycosidic aroma components from the perspective of aglycones and glycosides, respectively.